2020
DOI: 10.1007/s40265-020-01461-2
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting CDK4/6 in Breast Cancer with Palbociclib, Ribociclib, and Abemaciclib: Similarities and Differences

Abstract: The cyclin-dependent kinase (CDK) 4/6 inhibitors belong to a new class of drugs that interrupt proliferation of malignant cells by inhibiting progression through the cell cycle. Three such inhibitors, palbociclib, ribociclib, and abemaciclib were recently approved for breast cancer treatment in various settings and combination regimens. On the basis of their impressive efficacy, all three CDK4/6 inhibitors now play an important role in the treatment of patients with HR+, HER2− breast cancer; however, their opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
170
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 234 publications
(222 citation statements)
references
References 119 publications
(137 reference statements)
6
170
0
2
Order By: Relevance
“…Importantly, the NGP cell lines that possessed CDK4 amplification were sensitive to palbociclib, providing predictive importance of this genomic lesion [10]. In addition to palbociclib, ribociclib and abemaciclib, the other CDK4/6 inhibitors, have significantly prolonged the progression-free survival (PFS) of patients with advanced breast cancer [11]. As several clinical trials in other tumor types are ongoing, more information on predictive biomarkers for optimal treatment strategies for neuroblastomas will be made available in due course.…”
Section: Cdk4mentioning
confidence: 99%
“…Importantly, the NGP cell lines that possessed CDK4 amplification were sensitive to palbociclib, providing predictive importance of this genomic lesion [10]. In addition to palbociclib, ribociclib and abemaciclib, the other CDK4/6 inhibitors, have significantly prolonged the progression-free survival (PFS) of patients with advanced breast cancer [11]. As several clinical trials in other tumor types are ongoing, more information on predictive biomarkers for optimal treatment strategies for neuroblastomas will be made available in due course.…”
Section: Cdk4mentioning
confidence: 99%
“…Maximum concentration (C max ) is achieved within hours in all cases and the half-life within two days. Only for abemaciclib the saturation of drug absorption supported a twice-daily dosing regimen [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…Abemaciclib exerts less hematological toxicity, and it does not require dose interruptions, being gastrointestinal the most common dose-limiting toxicity [ 73 , 74 ]. Preclinical studies have shown that continuous administration of abemaciclib reduced tumor growth more efficiently compared with an intermittent schedule [ 72 ]. Abemaciclib also induces high senescence in BC cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…According to the pivotal role of CDK4 and CDK6 in driving cell cycle progression through the G1 phase of the cell cycle, the most prominent effect of all CDK4/6i is the block of cell proliferation [ 41 ]. Biochemically, this cell cycle blockage is accompanied by the inhibition of Rb phosphorylation, an event that can be observed both in vitro and in vivo [ 41 , 49 ]. Therefore, it has been postulated that tumors with alteration in proteins regulating the progression through the G1 phase of the cell cycle will be the most sensitive to these inhibitors.…”
Section: Mechanism Of Action Of Cdk4/6 Inhibitorsmentioning
confidence: 99%
“… Information have been retrieved from [ 41 , 42 , 43 , 49 ]: Abbreviations: NR, Not Reported, nM, nanoMolar. …”
Section: Figurementioning
confidence: 99%